Unified approach for the total aynthesis of Bis-THF C-15 acetogenins: a chloroenyne from laurencia majuscula, laurendecumenyne B and laurefurenynes A/B - Senapati, Sibadatta; Unmesh, Nivedya A.; Shet, Manoj N.; Ahmad, Iram; Ajikumar, Nandu; Ramana, Chepuri V. (Synthesis-Stuttgart, 2021)
A highly diastereoselective total synthesis of several bis-THF C-15 acetogenin natural products, chloroenyne from Laurencia majuscula, laurendecumenyne B, and laurefurenyries A/B, is reported. Additionally the synthesis of an advanced intermediate reported in the earlier total synthesis of (E/Z)-elatenynes (formal synthesis) is described. The salient features in the synthesis include epoxide opening, Birch reduction, Sharpless asymmetric dihydroxylation-cycloetherification, S(N)2 halogenation, and a relay cross metathesis.
Keywords: bis-THF C-15 acetogenins; carbohydrate building block; relay-cross-metathesis; S(N)2 halogenation; Sharpless asymmetric dihydroxylation-cycloetherification